The Influence of Tax Socialization, Education Level, and Taxpayer Awareness on Taxpayer Compliance in Paying Land and Building Tax in UDP Duren Sawit East Jakarta - Abbas, Yeni Elfiza; Weka, Anicetus (Akuntansi: Jurnal Akuntansi Integratif, 2024)
This is a quantitative exploration using an associative approach that was conducted at the UPPPD Duren Sawit Office in East Jakarta. This study aims to determine the effects of duty socialization, education status, and tax-prayer mindfulness on tax-prayer compliance in paying Land and Building Tax. The exploration is useful for observers of the Supreme Audit Agency, adding knowledge for observers of the Supreme Audit Agency carrying out checkups of taxpayer compliance in payment. The exploration increases knowledge for observers of the Supreme Audit Agency carrying out checkups of taxpayer compliance in payment. The exploration increases knowledge for observer This exploration increases knowledge and aids observers at the Supreme Audit Agency in auditing taxpayer compliance with payments. The data system related to the problem of the study was carried out using the questionnaire system. The study findings from 103 participants revealed that informing individuals about taxes does not affect their compliance with tax regulations. This can be observed from the t-test results, where the calculated t-value is 6.6023 and 2.826 is greater than 1.66023. The influence of tax socialization, level of education, and taxpayer awareness on compliance can be observed together through the F test. The calculated F value, greater than 20,623 and 3,087, highlights their noteworthy impact. The recommendation in this research suggests that the government should enhance adherence to the payment of Land and Building Tax by creating comprehensive, transparent, and user-friendly billing regulations aligned with current circumstances. Regulations are distributed to both taxpayers and tax collectors to enhance compliance and promote awareness regarding the payment of PBB-P2 taxes. Tax collectors handle PBB-P2 payments responsibly by promptly depositing them into the state treasury without any misuse.